Analisis Kesulitan Belajar Membaca (Disleksia) Siswa Kelas III SDIT Latansa Cendekia - Septy Nurfadhillah; Sa’odah Sa’odah; Gilang Ramadhan; Hasanah Dwi Wahyuni; Luthfiah Andriliani; Luthfia Nur Maulida; Nabilah Dwi Safitri; Ratri Hersita Dewi; Shinta Anjani Nura; Sabgi Wulan Septiara; Tiara Nur Cahyani; Vhaliesca Daffah (Journal on Education, 2024)
Education has a very important role in the progress of a nation. This research aims to reveal the history and development as well inclusive education problems. Inclusive schools provide appropriate educational programs, challenging, but appropriate to each student's abilities and needs as well as assistance and the support that teachers can provide so that children are successful. Method The research used in this research is descriptive qualitative. Data results were obtained from observations and interviews. By interviewing class III teachers at SDIT Latansa Scholar, this was done using a guide interview to get information about inclusive education at SDIT Latansa School. From the results of observations and interviews, the inclusion of students at this school is good, there are students who can carry out their own activities, but there is still assistance from the teacher. By joining a regular (non-special school) school, it provides an opportunity for them to be able to socialize with children who are growing normally to help the child's emotional development so that they do not become inferior children, and even consider themselves the same as other children. This is the basis on which inclusive education is implemented.